A convenient approach to difluoromethylated all-carbon quaternary centers via Ni(ii)-catalyzed enantioselective Michael addition. Issue 35 (25th May 2018) - Yu, Xuan; Bai, Hui; Wang, Dong; Qin, Zhaohai; Li, Jia-Qi; Fu, Bin
Abstract : Ni(ii )-catalyzed enantioselective Michael addition afforded compounds with all-carbon quaternary stereogenic centers featuring a CF2 H group in good enantioselectivities. Abstract : A Ni(ii )-catalyzed enantioselective Michael addition of 2-acetyl azarenes with β-difluoromethyl substituted nitroalkenes was successfully realized, which afforded chiral CF2 H-containing compounds in good enantioselectivities (up to 93% ee ). This protocol provides a new convenient approach to all-carbon quaternary stereogenic centers featuring a CF2 H group.